Optimization of spot weld joining parameters for dissimilar plate materials through finite element model updating and response surface methodology - Rosmaliza, Mat Yaacob; Muhammad Zikri, Japri; N.A.Z., Abdullah; Mohd Shahrir, Mohd Sani; Muhamad Norhisham, Abdul Rani; Arbintarso, Ellyawan Setyo (UiTM Press, 2024)
The utilization of dissimilar materials in manufacturing processes, especially in the automotive and aerospace industries, offers substantial benefits such as weight reduction, improved fuel efficiency, and enhanced mechanical properties. However, the optimization of spot welds for these dissimilar materials presents significant challenges due to their diverse physical and chemical properties. This research seeks to optimize the input properties of finite element models (FEM) for spot welding dissimilar plates by utilizing model updating and response surface methodology (RSM). These techniques refine the computational models to more accurately reflect experimental data. Correlation techniques were used to compare Experimental Modal Analysis (EMA) and Finite Element Analysis (FEA), revealing that CWELD has a 1.21% higher correlation compared to CBAR and CBEAM. Despite this, CWELD was chosen for the updating process due to its similarity with the actual joining structure. Subsequent Finite Element Model Updating(FEMU) effectively reduced the error in natural frequency prediction from 6.87% to 4.04%. Additionally, the RSM approach successfully optimized the structural design variables, achieving a desirability rate of 0.972 and showing a significant reduction in percentage error to 5.02% from 6.87%. This study offers valuable insights into the effective enhancement of dynamic properties for dissimilar plate structures, highlighting the importance of both optimization techniques in achieving superior accuracy in structural analysis and design.